2012
DOI: 10.1007/s00247-011-2338-2
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced sonography of malignant pediatric abdominal and pelvic solid tumors: preliminary safety and feasibility data

Abstract: Background Little information exists regarding pediatric contrast enhanced ultrasonography. Objective To assess the safety and feasibility of contrast enhanced ultrasonography of pediatric abdominal and pelvic tumors. Materials and Methods This prospective study included eight boys and five girls (mean age, 10.8 years) with abdominal or pelvic tumors. Cohorts of three subjects underwent ultrasound with perflutren contrast agent at escalating dose levels.Neurological and funduscopic examination, electrocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 32 publications
0
26
1
Order By: Relevance
“…Contrast enhanced ultrasound is a promising new technology that has been described in evaluation of the kidneys, as well as abdominal and pelvic tumors in children [ 46 ]. Further investigation will be required to determine if this technique can be applied to the evaluation of congenital Müllerian anomalies.…”
Section: D Ultrasoundmentioning
confidence: 98%
“…Contrast enhanced ultrasound is a promising new technology that has been described in evaluation of the kidneys, as well as abdominal and pelvic tumors in children [ 46 ]. Further investigation will be required to determine if this technique can be applied to the evaluation of congenital Müllerian anomalies.…”
Section: D Ultrasoundmentioning
confidence: 98%
“…The two agents already available in the USA, Optison® (General Electric Healthcare, Princeton, NJ) and Definity® (Lantheus Medical Imaging, North Billerica, MA), were approved many years ago by the U.S. Food and Drug Administration for adult echocardiography and thus are already on the pharmacy formulary of many institutions. McCarville et al [4] reported safe and successful application of intravenous Optison® enhanced US for evaluation of solid tumors in children. Because pediatric use and safety data were available for this contrast agent, the task force, independent of manufacturer support, endorsed further exploration of Optison® for the purpose of CEUS.…”
Section: Introductionmentioning
confidence: 98%
“…No change attributable to the ultrasonography contrast was detected on neurological, funduscopic examination, electrocardiography and continuous pulse oximetry. 23 In an older study of contrast-enhanced echocardiography examining 20 patients, no children showed adverse haemodynamic reactions, change in taste or flushing episodes, whereas headache was reported in only 3 cases. 25 Based on these studies, ultrasonography contrast agents can be considered equally safe for adults and children.…”
Section: Safetymentioning
confidence: 99%
“…22 In the paediatric population, limited studies evaluated the safety profile of ultrasonography contrast agents. [23][24][25][26][27][28] The largest series involved 167 CEUS examinations using SonoVue™ in 137 children, which documented 1 (0.6%) severe allergic reaction. However, no other haemodynamic and oxygenation status changes were documented in this study, and no other subjective complaints were recorded following the CEUS examination.…”
Section: Safetymentioning
confidence: 99%